Block and unplugged programming can be mutually beneficial: A study of learning activities in a 6th grade class in Norway - Heim, Greta; Wang, Oskar Jensen (Frontiers in Education, 2023)
In the new Norwegian national curricula, programming and interdisciplinary work have been introduced as two central elements. Furthermore, computational thinking is part of the core elements of the mathematics curriculum. In this paper, we present the findings from a small-scale study within the subjects of mathematics and food and health. The aim was to see if these two subjects could be used as an arena for working with parts of computational thinking, in this case algorithmic thinking and collaboration, and expanding the students’ understanding of what programming can be. We think there is a gap in the research regarding this topic, and therefore we wanted to look into this. The students who took part in the study carried out two lessons, one in each subject. In mathematics, the focus was on block programming, while food and health can be seen as unplugged programming. Our findings are based on feedback from 36 students and observations from the lessons. The main finding is that most of the students could not see a link between programming and food and health. Only seven students expressed something that indicated that they did see a link. Thus, it seems like most of the students could not see similarities between the algorithmic thinking in block programming and recipes in food and health.